Colon-Targeted Oral Drug Delivery Systems: A Review - Choudhary, Lokesh; Jain, Amit; Agarwal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2020)
The colon is a site where both local and systemic delivery of drugs can take place. Local delivery allows topical treatment of inflammatory bowel disease. However, treatment can be made effective if the drugs can be targeted directly into the colon, thereby reducing the systemic side effects. This review, mainly compares the primary approaches for CDDS (Colon Specific Drug Delivery) namely prodrugs, pH and time dependent systems, and microbially triggered systems, which achieved limited success and had limitations as compared with newer CDDS namely pressure controlled colonic delivery capsules, CODESTM, and osmotic controlled drug delivery which are unique in terms of achieving in vivo site specificity, and feasibility of manufacturing process. New systems and technologies have been developed for colon targeting and to overcome pervious method’s limitations. Colon targeting holds a great potential and still need more innovative work. This review article discusses, in brief, introduction of colon, factor effecting colonic transition, colonic diseases and the novel and emerging technologies for colon targeting.